Android-Based Digital Media Analysis as a Futuristic Pedagogic Implementation in Improving Early Childhood Self-Image - Nugroho, Rian Sri; Sauri, Sofyan; Nuryani, Pupun (International Conference on Elementary Education, 2021)
The use of media in learning is one of the conditions for the learning process. The times have resulted in a variety of media used in the educational process, especially when technology has begun to be recognized and used by many people in every aspect of life. Pandemic conditions like now require its use in the learning process, of course, with various benefits and challenges. Early childhood education is the smallest unit of formal education which must be a forum for forming strong character from the start so that it has a strong foundation. Self-image is one of the things that have a strong role in a person's personality, the form of an individual image is reflected in mental attitudes and behavior based on the results of experience which ultimately become the strength or characteristic of each individual.